Ractopamine hydrochloride and immunological castration in pigs. Part 1: Fresh belly characteristics for bacon processing and quality - Costa E Silva, Letícia Cristina [UNESP]; Barbosa, Roger Darros [UNESP]; Boler, Dustin Dee; Silveira, Expedito Tadeu Facco (FapUNIFESP (SciELO), 2017)
The effects of ractopamine and immunological castration on belly characteristics, processing yield, physicochemical and sensory quality of bacon were investigated from two crossbred pigs under different conditions of animal production, diet, management and slaughter arranged in factorial design using 2 ractopamine levels (0 and 7.5 ppm) and 3 genders (barrows, immunocastrated and gilts). Before processing, belly firmness, weight, length, width and thickness were measured, and then, bacon processing yield evaluated. After processing, bacon slices were digitally imaged and analyzed for lean meat and fat areas, pH, instrumental color of meat and fat, cooking loss and sensory quality. The ractopamine did not alter belly characteristics, but significantly increased the process yield and decreased cooking loss. Barrows and immunocastrated pigs showed firmer bellies, which could be advantageous for bacon processing and slicing. Barrows presented the highest total area of bacon slices. The results of this study indicate that both techniques ractopamine in the finishing diets and immunocastration of pigs can be combined with no further consequences for belly processing and to bacon quality and with some advantages.
Keywords: Bacon; Belly characteristics; Digital imaging; Immunological castration; Ractopamine hydrochloride; Sensory